Cell proliferation assay – method optimisation for in vivo labeling of DNA in the rat forestomach - Joksić Gordana (Sciendo, 2017)
The study of cell proliferation is a useful tool in the fields of toxicology, pathophysiology and pharmacology. Cell proliferation and its degree can be evaluated using 5-bromo-2′-deoxyuridine which is incorporated into the newly synthesized DNA. The aim of this study was the optimization of subcutaneous application of 5-bromo-2′-deoxyuridine implantation for continuous and persistent marking of proliferating cells in the rat forestomach. 3-tert-Butyl-4-hydroxyanisole was used as the agent that ensures cell proliferation. In order to determine the optimal dose for proliferating cells labeling, 5-bromo-2′-deoxyuridine doses of 50 mg, 100 mg, 200 mg or 350 mg were implemented 2 days prior to sacrifice by flat-faced cylindrical matrices. Immunohistochemical analysis using 5-bromo-2′-deoxyuridine in situ detection kit was performed for the detection of 5-bromo-2′-deoxyuridine labeled cells. The results showed that for adult rats, the optimum 5-bromo-2′-deoxyuridine dose is 200 mg per animal for subcutaneous application. The here described manner of 5-bromo-2′-deoxyuridine in vivo labeling provides a simple, efficient, and reliable method for cell labeling, and at the same minimizes stress to animals.